Analysis of Factors Influencing Mobile Payment Usage Behavior with Behavioral Intention as Moderating Variable - EMI BOKI; GRACE T. PONTOH; SYARIFUDDIN RASHID (International Journal of Multidisciplinary Research and Studies, 2023)
Abstract The purpose of this study was to examine and analyze the relationship between perceived usefulness and perceived risk on mobile payment usage behavior with behavioral intention as a moderating variable. The population in this study were all master of accounting students at the Faculty of Economics and Business at Hasanuddin University with a sample of 94 students. This research method uses Structural Equation Modeling (SEM) using PLS software. The type of data in this study is primary data in the form of a questionnaire containing the respondents' assessments. The results of this study indicate that perceived usefulness has a significant positive effect on mobile payment usage behavior, perceived risk has a significant positive effect on mobile payment usage behavior, behavioral intention can mediate the relationship between perceived usefulness and mobile payment usage behavior, behavioral intention can mediate the relationship between perceived risk and mobile payment usage behavior.